Memorability and Cognitive Errors in Recognizing Graffiti in Urban Environments: Results from a Field Experiment - O. V. Kruzhkova (Научный диалог)
The authors of vandalistic alterations to urban environments aim to make their works noticeable to the maximum number of observers in order to draw attention to their statements. However, from the perspective of the “inadvertent observer,” the visibility of unauthorized graffiti as elements of the urban landscape and their cognitive impact are not immediately evident. The objective of this study is to examine the perception of graffiti in the form of images and vandalized texts, focusing on their recognition and memorization by “inadvertent observers” in natural urban settings during a walking route. Participants in the field experiment (29 individuals aged 14 to 59) were asked to walk along a pedestrian route in the city center of Yekaterinburg. The direction of participants’ gaze was tracked using mobile eyetracking glasses. After completing the route, respondents selected unauthorized graffiti (both images and texts) encountered along the way from a set of alternatives presented in a questionnaire. It was found that unauthorized graffiti encountered along the route were most frequently recognized by participants aged 18 to 29, with no significant differences in recognition based on gender. A preference for recognizing images over texts was identified. Familiar and comprehensible graffiti, as well as those addressing atypical (particularly religious) themes, were recognized more readily. Cognitive errors (e.g., memory attribution errors) were linked to the widespread presence of typical graffiti in urban environments.